Penerapan Model Pembelajaran SOLE (Self Organized Learning Environments) Pada Hasil Belajar Peserta Didik Kelas XI IPA SMA Negeri 1 Bukittinggi Berbantuan Aplikasi Microsoft Teams - Sukma Roviani; Hadiyati Idrus; Marjoni Imamora Ali Umar; Artha Nesa Chandra (Edusainstika: Jurnal Pembelajaran MIPA, 2023)
This study aimed to determine whether students who used the Self Organized Learning Environments (SOLE) learning model using the Microsoft Teams application had better learning outcomes than students who used the face-to-face learning model. The post-trial-only control group design is a study design used in quasi-experimental studies. The population of this study was XI IPA SMA Negeri 1 Bukittinggi. Two classes are sampled, that is, experimental class XI IPA 7 and control class XI IPA 6, which are sampled through normality test, homogeneity test and population mean similarity test. The sampling method uses simple random sampling where the results of the analysis found that both classes of samples are normally distributed, have homogeneous variants and the average population class is the same. The 20-question final exam is a tested and analyzed research tool. The experimental class achieved an average overall score of 80.13 for the cognitive domain, while the control class got an average final test score of 77.28. For the affective domain, the average value of the experimental class was 73.19, while the average value of the control class was 71.61. For the psychomotor domain, the average value of the experimental class was 73.51, while the average value of the control class was 70.04. The research hypothesis explains that "the learning outcomes of students who apply the SOLE (Self Organized Learning Environments) learning model assisted by the Microsoft Teams application are better than the learning outcomes of students who apply the direct learning model" formulated based on research results.